Optical coherence tomography in the diagnosis of myocardial infarction with non-obstructive coronary arteries - Iwańczyk, Sylwia; Woźniak, Patrycja; Araszkiewicz, Aleksander; Grygier, Marek; Klotzka, Aneta; Lesiak, Maciej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a working diagnosis and requires identification of the underlying causes to optimize treatment, improve prognosis, and prevent the recurrence of myocardial infarction. According to the literature, the prognosis of patients diagnosed with MINOCA is comparable to the group of patients with myocardial infarction (MI) and significant stenosis of the coronary arteries. Intracoronary imaging is a crucial diagnostic tool used in identifying epicardial causes of MINOCA that are not visible in coronary angiography. Optical coherence tomography (OCT) provides the highest spatial resolution, simultaneously allowing detailed visualization of plaque pathology in individuals with MINOCA and identifying the cause of MI in up to 80% of patients. Common causes of a MINOCA may include plaque disruption, spontaneous coronary artery dissection (SCAD), coronary artery spasm, and coronary thromboembolism. The optimization of pharmacological treatment in this group of patients, especially dual antiplatelet therapy and statins, improves the prognosis. Data on the indications for invasive treatment of patients with MINOCA based on OCT findings are insufficient. There is a strong need for research comparing treatment strategies, especially in high-risk lesions visualized in OCT. The main aim of this review is to demonstrate the usefulness of OCT in determining the mechanism of MINOCA.